KAJIAN DAN PENERAPAN GARAP SINDHENAN PADA GENDHING PAMEKASAN WUDHAR SLENDRO SANGA - Ar Ribath Diin Nikhmah; Suraji (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2023)
This article entitled "Pamekasan Wudhar, Gendhing Kethuk 2 Kerep Minggah 4 Laras Sléndro Pathet Sanga: A Study of Garap Sindhèn" analyses, presents and describes the sindhènan of the music in it. The problem in this art thesis is the garap and sindhènan analysis of Gendhing Pamekasan Wudhar. This research uses a type of qualitative research, the method used is qualitative method. Data were collected by interview, observation, and literature study. This problem is analysed through the concept of garap by Rahayu Supanggah, the concept of mungguh by Bambang Sosodoro, and the concept of padhang-ulihan by Martopengrawit. The results of the research on Gendhing Pamekasan Wudhar found that the garap contained in this music includes the placement of sindhènan techniques, garap mandheg, and sindhènan gawan cengkok puthut gelut. The application of the sindhènan céngkok puthut gelut garap is used as a varied garap in this music. Sindhènan gawan cengkok puthut gelut that is not worked on mandheg makes this gending has a unique sindhènan arrangement. As a pesindhèn, she is required to be responsive in presenting sindhènan. This can be supported by understanding the placement of padhang-ulihan so that it can place the application of wangsalan and abon-abon properly. In addition, paying attention to the application of céngkok and wiledan that must be in accordance with the character of the song being presented, the presentation of the right sindhènan technique is also an important thing to note for a pesindhèn.